A violência estrutural e a saúde bucal dos adolescentes no Espírito Santo - Brasil - Vieira Netto, Moysés Francisco (2007)
This study deals with the problematic of the conditions of buccal health of the Brazilian adolescents by means of a social approach and a close relation with the process of structural violence by means of perceptions, knowledge and attitudes of the municipal coordinators of buccal health of Espirito Santo (ES) or references techniques in the area. On theoretical terms, it bases on the studies on the structural violence and its relation with the health and, more specifically, on the theory of Minayo on the manifestations of this modality of violence, considering that, in the contemporary world, the confrontation of violence needs to consider that it does not exist itself in a lonely scene, but as a multiple violence. This way, its manifestations have reached the public administrations that omit, neglect and even exclude people or groups of people from the right to life-quality, from the full exercise of the citizenship. The buccal health is a victim of the exculpatory and inefficient public administrations that collide in big damages on the adolescents. The results of the last survey of the conditions of buccal health of the Brazilian, carried through for the Health department in 2003, “SB Brazil”, had disclosed the necessity of the study with the adolescents, which in the age of eighteen years possess only half of teeth, a rellevant problem and an example of structural violence (institucional). It is a study of case and a exploratory inquiry with a interpretativist approach by means of the comprehensive sociology, based on the principles of the comunicative philosophy. Then, the study it understands the structural violence whose clipping is in its manifestation of the conditions of buccal health of the adolescents, with priority to understand the social reality lived by these citizens and its relations with the organization (management) of the public dental services from the cities of Espírito Santo. It is treated, therefore, as one research of quantity and quality approach on the basis of the proposals of the triangulation method, with the interlocution of these boardings and the participation of the researcher, defended by the researchers Minayo, Assis and Souza. An important point was the unfamiliarity of the municipal coordinations of buccal health ES concerning the dimension of the problems of buccal health with the adolescents and the narrow relation of these with the process of odontological work. The coordinations are not sensible to the perception of the problem nor perceive the manifestation of the violence in its acts as managers. So, here it’s a fertile and productive field of structural violence that, in a “occult” form, has firmed as practical daily, as if it was not violence, or same, as if it did not exist measured capable it withhold it. During the research, diverse problems appeared, which relevance and complexity could not have been explored in this paper, because they need others researchs that establishes deeper relations of study.